Lower Limb Deformity and Gait Deviations Among Adolescents and Adults With X-Linked Hypophosphatemia - Mindler, Gabriel T.; Kranzl, Andreas; Stauffer, Alexandra; Kocijan, Roland; Ganger, Rudolf; Radler, Christof; Haeusler, Gabriele; Raimann, Adalbert (Frontiers in Endocrinology, 2021)
Background: X-linked hypophosphatemia (XLH) is a rare genetic disorder characterized by lower limb deformity, gait and joint problems, and pain. Hence, quality of life is substantially impaired. This study aimed to assess lower limb deformity, specific radiographic changes, and gait deviations among adolescents and adults with XLH. Design: Data on laboratory examination and gait analysis results were analyzed retrospectively. Deformities, osteoarthritis, pseudofractures, and enthesopathies on lower limb radiographs were investigated. Gait analysis findings were compared between the XLH group and the control group comprising healthy adults. Patients and controls: Radiographic outcomes were assessed retrospectively in 43 patients with XLH (28 female, 15 male). Gait analysis data was available in 29 patients with confirmed XLH (28 women, 15 men) and compared to a healthy reference cohort (n=76). Results: Patients with XLH had a lower gait quality compared to healthy controls (Gait deviation index GDI 65.9% +/- 16.2 ). About 48.3% of the study population presented with a greater lateral trunk lean, commonly referred to as waddling gait. A higher BMI and mechanical axis deviation of the lower limbs were associated with lower gait scores and greater lateral trunk lean. Patients with radiologic signs of enthesopathies had a lower GDI. Conclusions: This study showed for the first time that lower limb deformity, BMI, and typical features of XLH such as enthesopathies negatively affected gait quality among adolescents and adults with XLH.